COMPARATIVE STUDY OF THE CONSTITUTIONAL COURT AS A GUARDIAN OF THE CONSTITUTION BETWEEN INDONESIA AND GERMANY - Chatrine Sabendi Putri; Muhammad Rafi Darajati (Law Faculty of Universitas Bandar Lampung, 2022)
After years of being formed, the Indonesian Constitutional Court is considered to have carried out its duties and functions well. However, if we look further, there are still shortcomings and several things that the Indonesian Constitutional Court has not accommodated in carrying out its duties and functions compared to the German Constitutional Court which is known to the world as one of the Constitutional Courts which is often used as a reference by other countries in the establishment of the Constitutional Court. This article will discuss the differences between Indonesian Constitutional Court and German Constitutional Court which aims to sort out the positive things that can be an improvement material for the Indonesian Constitutional Court to strengthen the Indonesian Constitutional Court. This writing uses a normative writing method with a comparative approach and a historical approach. The results of this study show that there are several arrangements from the German Constitutional Court that can actully be applied by the Indonesian Constitutional Court such as the authority of constitutional complaints and constitutional questions, arrangements regarding the expansion of the applicant party in the application for dissolution of a political party to the Constitutional Court, and regarding the elimination of re-election for a constitutional judge and also about the addition of their term of office.